PENGARUH PENETAPAN HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA SELEBRITI ASIAN&SUKI RESTAURANT PEKANBARU - Maryam, Zaza; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The research conducted at Selebriti Asian&Suki Restaurant Pekanbaru where located in Jl. Sudirman No.426 Lt 1, Gedung Star City Square. The problem in this study is number of buyers has decreasing, percentage of target achievement has decreased, and  the failure of the company’s sales target has not been achieved, this study aims to determine the effect of pricing and service quality on consumer satisfaction Selebriti Asian&Suki Restaurant Pekanbaru . In this study use quantitive descriptive with SPSS program. The population in this is are consumers at Selebriti Asian&Suki Restaurant. The sampling technique chosen is slovin Formula with a sample 97 respondents.            Hypothesis testing uses a simple linear analysis method and multiple analysis with result showing that pricing and service quality have a positive and significan on consumer satisfaction Selebriti Asian&Suki Restaurant. With the calculation of the coefficient of determination (R2) pricing on consumer satisfaction of R square is 0,450 or 45% and service quality on consumer satisfaction the value of R square is 0,478 or 47,8% and coefficient of determination R square pricing and service quality on consumer satisfaction the value of R is 0,607. This show that the pricing and service quality gives an effect of 60,7% on consumer satisfaction at Selebriti Asian&Suki Restaurant, while remaining 39,3% is effected by other variables that are not examined in this study. Key words: Pricing, Service Quality and Consumer Satisfaction